A novel Lozenge gene in silkworm, Bombyx mori regulates the melanization response of hemolymph. Issue 1 (November 2015) - Xu, Man; Wang, Xue; Tan, Juan; Zhang, Kui; Guan, Xi; Patterson, Laurence H.; Ding, Hanfei; Cui, Hongjuan
Abstract Runt-related (RUNX) transcription factors are evolutionarily conserved either in vertebrate or invertebrate. Lozenge (Lz), a members of RUNX family as well as homologue of AML-1, functions as an important transcription factor regulating the hemocytes differentiation. In this paper, we identified and characterized RUNX family especially Lz in silkworm, which is a lepidopteran model insect. The gene expression analysis illustrated that BmLz was highly expressed in hemocytes throughout the whole development period, and reached a peak in glutonous stage. Over-expression of BmLz in silkworm accelerated the melanization process of hemolymph, and led to instantaneously up-regulation of prophenoloxidases (PPOs), which were key enzymes in the melanization process. Further down-regulation of BmLz expression by RNA interference resulted in the significant delay of melanization reaction of hemolymph. These findings suggested that BmLz regulated the melanization process of hemolymph by inducing PPOs expression, and played a critical role in innate immunity defense in silkworm.